2010
DOI: 10.1016/j.chemosphere.2009.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Fate of aerobic bacterial granules with fungal contamination under different organic loading conditions

Abstract: Aerobic sludge granulation is an attractive new technology for biological wastewater treatment. However, the instability of aerobic granules caused by fungal growth is still one of the main problems encountered in granular bioreactors. In this study, laboratory experiments were conducted to investigate the fate and transformation of aerobic granules under different organic loading conditions. Bacterial granules (2-3mm) in a poor condition with fungi-like black filamentous growth were seeded into two 1L batch r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Meanwhile, the SVI 5 decreased from 250 to 100 ml/g in R1 and from 200 to 40 ml/g in R2. However, the SVI 5 remained about twice as large as SVI 30 for the R1 sludge throughout the rest of the SBR test. This agreed with the microscopic observation that the sludge in R1 remained in the form of suspended flocs.…”
Section: Comparison Of the Sludge Between The Two Sbrsmentioning
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the SVI 5 decreased from 250 to 100 ml/g in R1 and from 200 to 40 ml/g in R2. However, the SVI 5 remained about twice as large as SVI 30 for the R1 sludge throughout the rest of the SBR test. This agreed with the microscopic observation that the sludge in R1 remained in the form of suspended flocs.…”
Section: Comparison Of the Sludge Between The Two Sbrsmentioning
confidence: 91%
“…Thus, as demonstrated in Phase 1, it is apparently impossible for granules to grow and become dominant in a reactor without selective discharge. Discharge of suspended small and loose sludge flocs removes these competitors from the system and makes the substrates more available for the biomass in attached-growth form, which leads to granulation [30].…”
Section: Comparison Of the Sludge Between The Two Sbrsmentioning
confidence: 99%
“…However, although large granules can be formed more quickly at a higher F/M, the large sizes of granules are not desirable for the wastewater treatment purpose. It has been found that large granules usually are less stable and have more problems in long-term operation, such as breakage, erosion, floating, and fungal contamination [30,31]. image; bottom: schematic).…”
Section: Microbial Population Dynamics During Aerobic Granulation At mentioning
confidence: 99%
“…Sequences belonging to this group have previously been retrieved from aerobic granules degrading chloroanilines, methyl tert -butyl ether, tert -butyl alcohol and simple carbon sources such as glucose, acetate and propionate [6], [16], [23], [24], [43], [47], [50], [51], [52]. Particularly, Pseudoxanthomonas sp., Xanthomonas sp., Rhizobales sp., Acidovorax sp., and Nitrospira sp., which were the closest relatives of the sequences from bands S1, S3, S4, S6, and S8, respectively, have been previously found in aerobic granules [3], [16], [24], [46], [47], [48], [52]. Interestingly, these species were identified in the aerobic granules as being involved on volatile fatty acids and amino acids uptake, on exopolysaccharides production and on the nitrification and denitrification processes [3], [47].…”
Section: Resultsmentioning
confidence: 99%